Hypoxic stress and cancer: Imaging the axis of evil in tumor metastasis - Avni, Reut (2011)
Tumors emerge as a result of sequential acquisition of genetic, epigenetic, and somatic alterations promoting cell proliferation and survival. The maintenance and expansion of tumor cells relies on their ability to adapt to changes in their microenvironment, along with acquisition of the ability to remodel their surroundings. Tumor cells interact with two types of interconnected microenvironments, the metabolic cell autonomous microenvironment and the non-autonomous cellular-molecular microenvironment comprising interactions between tumor cells and the surrounding stroma. Hypoxia is a central player in cancer progression, affecting not only tumor cell autonomous functions such as cell division and invasion, resistance to therapy and genetic instability, but also non-autonomous processes such as angiogenesis, lymphangiogenesis and inflammation, all contributing to metastasis. Closely related microenvironmental stressors, affecting cancer progression include in addition to hypoxia, also elevated interstitial pressure and oxidative stress. Non invasive imaging offers multiple means for monitoring the tumor microenvironment and its consequences, and can thus assist in understanding the biological basis of hypoxia and microenvironmental stress in cancer progression, and in development of strategies for monitoring therapies targeted at stress induced tumor progression.